Pengaruh Pengetahuan Dan Budaya Terhadap Perawatan Masa Nifas Pasca Persalinan Normal Dan Sectio Caesarea Di Wilayah Kerja Puskesmas Danau Indah - Lina Kurnia; Resi Galaupa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
The postpartum period is a critical period in the process of survival for mothers and newborns. In general, maternal and newborn deaths occur in the first month postpartum. Therefore, during the postpartum period, intensive health care is needed to prevent the risk of morbidity and mortality for mothers and newborns. Postpartum care is carried out both for postpartum mothers with normal deliveries and by cesarean section (SC). The purpose of this study was to determine the relationship between knowledge and culture on the Care of the Puerperal Period after Normal Childbirth and Sectio Caesarea. The research design used a cross sectional study with a total sample of 32 people obtained through a purposive sampling technique. From the chi square statistical test on the knowledge variable, a p value of 0.008 was obtained where the p value <0.05 with a degree of significance Î± = 0.05 and for the cultural variable a p value was obtained of 0.020 where a p value <0.05 with a degree of significance Î± = 0 .05 then the null hypothesis is rejected and the alternative hypothesis is accepted which means there is a relationship between knowledge and culture with postpartum care. It is recommended that health workers always provide postpartum mothers with education regarding breast care.